Дослідження реакції озону з метилфенілкарбінолом в оцтовій кислоті - Бушуєв, А. С.; Колбасюк, О. О.; Галстян, Г. А. (НТУ "ХПІ", 2014)
Досліджено реакцію озону з метилфенілкарбінолом – напівпродуктом реакції окиснення етилбензену. Показано, що при температурі 15оС озон реагує переважно по бічному ланцюгу з утворенням ацетофенону (95%) і лише ~5% метилфенілкарбінолу руйнується за ароматичним кільцем. З підвищенням температури кількість ацетофенону зменшується, переважно за рахунок його подальшого окиснення до бензойної кислоти. Вивчена макрокінетика процесу, запропонована хімічна схема перетворень, яка задовільно пояснює одержані експериментальні дані.

The reaction of ozone with methylphenylcarbinol who is intermediate in ethylbenzene oxidation reaction was researched. It is shown that at 15oC ozone reacts predominantly by side chain to form acetophenone (95%) and only about 5% of methylphenylcarbinol destroyed by the aromatic ring. In result increasing temperature oxidation process selectivity to acetophenone is reduced, due to its oxidation to benzoic acid, benzene ring remains intact under these conditions. Benzoic acid in the experiments is rather stable substance and therefore it the final product in the cycle transformations of ethylbenzene.Oxidation of methylphenylcarbinol in terms of the experiments passes as a non-chain radical reaction.Variation of ozone concentration in the gas mixture has almost no effect on the yield of acetophenone. Defined effective constants of reactions of ozone with methylphenylcarbinol and its oxidation products. Received the microkinetics of the process, proposed scheme of chemical transformations, which satisfactorily explains the obtained experimental data.
Research of reaction of the ozone with methylphenylcarbinol in the acetic acid
Keywords: хімічна промисловість; процеси окиснення; алкілбензени; оксигенвмісні похідні; ацетофенон; бензойна кислота; константа швидкості; ozone; oxidation; acetophenone; benzoic acid; effective constant